Comparison of polymer-based slag-mud slurries used for drilling jobs of steam stimulated wells in the Lagunillas oilfield (Venezuela). (23rd November 2020) - Martín-Del-Río, Juan Jesús; Márquez, G.; Flores-Alés, V.; Romero, E.; Rey, O.; Villanueva, M. Guzmán
The mud-to-cement conversion or 'slag-mix' technology displays several advantages when compared to conventional well cementing operations. This alternative method means to combine drilling fluids, accelerators, and finely granulated slag as the hydraulic material. Steam injection is commonly used to improve crude oil production in the Lagunillas field (state of Zulia, NW Venezuela). This work compares the use of two slag-mix systems containing two polymer-based drilling muds during cementing of injection wells: an aqueous drilling fluid and an oil-in-water emulsion mud. After comparing the use of the two study drilling mud systems with a typical lignosulfonate slag-mix system, it can be stated that both systems may be suitable to be used in the application of the mentioned-above technology in steam stimulated wells. The aqueous formulations under study and a typical slag-mud slurry containing lignosulfonate show relatively similar values for most physic-mechanical properties. In contrast, the slag-mix emulsion system under consideration shows distinctive rheological and filtration behaviours compared to the other study polymer-based slag-mud slurry, but similar mechanical properties. [Received: April 26, 2019; Accepted: August 1, 2019]